Ultramafic pseudotachylytes in high-pressure metamorphogenic peridotite from Luobusha, Tibet: a record of crustal paleo-earthquakes - Zhang, Haoran; Xu, Xiwei; Yang, Saihong (Frontiers in Earth Science, 2023)
In this paper we report an occurrence of ultramafic pseudotachylyte which is fault-rock evidence of palaeo-earthquakes from the Luobusha ophiolite complex, in Yarlung Zangbo suture zone. The pseudotachylytes form hairline-thin aphanitic veinlets and vein networks bounded by micro-damagezones cutting through the host harzburgite, and in places forming flow banding. The pseudotachylyte veins are dominated by close-knit ultrafine grained minerals consisting of olivine, ortho-pyroxene, serpentine, spinel and magnetite, cemented by an extremely fine matrix. As the primary component of the pseudotachylyte veins, olivine occurs as microphenocryst showing zoning from core to rim and as irregularly-shaped microlite immersed in the interstitial material. Zoned crystals of olivine developed with Mg-rich cores and more Fe-rich rims. Microlites diagnostic of crystallization in quenched melt include dendritic, skeletal and poikilitic olivine crystals, which are typical of ultramafic pseudotachylyte. The olivine microlites contain higher amounts of Ca, Al and Cr, but a lower Ni content compared with the host harzburgite olivine. Irregularly shaped chrome spinel crystals are chemically zoned as well, indicating a Fe-rich rim overgrowth. Ni sulfide droplets interspersing among the matrix imply melt occurrence. The presence of a micro-fibrous and microvesicular interstitial matrix also indicates a melting-related origin. Ultracataclastite veins associated with pseudotachylyte transecting serpentine are observed, which convey that heat was generated during rapid comminution and injection.The characteristic petrography, microtextures and chemical inhomogeneties meet the criteria of ultramafic pseudotachylyte and reveal mixed genesis of a combination of crushing and melting. The development of extremely tiny globular prograde serpentine inclusions (~100nm) in the olivine mircolites are ascribed to dehydration reaction of serpentine to olivine within the pseudotachylyte. The Luobusha metamorphogenic peridotite was subjected to serpentinization after having emplaced in the crust and subsequently to high pressure metamorphism. The pseudotachylytes were generated in the crust after the high-pressure metamorphism and did not went down to a deeper depth . Flash ultra-comminution associated with frictional heating may release fluids by localized heat-driven prograde reactions in the crust.